Metagenomics in Polluted Aquatic Environments - Cardoso, Alexander M.; Coutinho, Felipe H.; Coutinho, Felipe H.; Silveira, Cynthia B.; Ignacio, Barbara L.; Vieira, Ricardo P.; Salloto, Gigliola R.; Clementino, Maysa M.; Albano, Rodolpho M.; Paranhos, Rodolfo; Martins, Orlando B. (IntechOpen, 2012)
None